Hypomethylation of FAM63B in bipolar disorder patients. Issue 1 (December 2016) - Starnawska, Anna; Demontis, Ditte; McQuillin, Andrew; O'Brien, Niamh; Staunstrup, Nicklas; Mors, Ole; Nielsen, Anders; Børglum, Anders; Nyegaard, Mette
Abstract Bipolar disorder (BD) and schizophrenia (SZ) are known to share common genetic and psychosocial risk factors. A recent epigenome-wide association study performed on blood samples from SZ patients found significant hypomethylation ofFAM63B in exon 9. Here, we used iPLEX-based methylation analysis to investigate two CpG sites inFAM63B in blood samples from 459 BD cases and 268 controls. Both sites were significantly hypomethylated in BD cases (lowestp value = 3.94 × 10−8 ). The methylation levels at the two sites were correlated, and no strong correlation was found with nearby single nucleotide polymorphisms (SNPs), suggesting that methylation differences at these sites are not readably picked up by genome-wide association studies. Overall, FAM63B hypomethylation was found in BD patients, thus replicating the initial finding in SZ patients. This study suggests thatFAM63B is a shared epigenetic risk gene for the two disorders.